Analyze the correlation of hafiz qur'an and yaumiah worship toward the level of math anxiety - D P Wardani; S Prabawanto; T Herman (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Anxiety towards mathematics is often experienced by students in the learning process,especially mathematics. High level of mathematical anxiety can affect the process and studentlearning outcomes. High levels of anxiety can make student learning outcomes low. This researchis aimed to analyze the relation of hafiz qur'an and yaumiah worship to the level of math anxiety.Subjects in this study are junior high school students, who in addition to learning he also doactivities memorization Al-Qur'an, other than that the students are also very maintainingyaumiahnya worship, such as wajib prayers and sunah, fasting sunah, read qur'an and zikir. Thisresearch are descriptive qualitative research. The researchers collected data throughquestionnaires of anxiety mathematics, sheet of memorization Al-Qur'an, and sheet of muttabaahyaumiah, then the researchers analyzed the data collected. The results are that: (1) Quantity ofhigh zikr can reduce anxiety in learning mathematics, to the level of medium learning anxiety,and (2) obligatory prayers are always done and on time can affect the level of anxiety studentsin doing math problems, to the level of medium anxiety.